The Barcelona-Asymptomatic Intracranial Atherosclerosis (AsIA) study: Subclinical cervico-cerebral stenosis and middle cerebral artery pulsatility index as predictors of long-term incident cognitive impairment. (November 2020) - Crespo-Cuevas, A.M.; Canento, T.; Hernández-Perez, M.; Cáceres, C.; González, A.; Ispierto, L.; Mataró, M.; Vilas, D.; Planas-Ballvé, A.; Martin, L.; Muñoz-Ortiz, L.; Arenillas, J.F.; et al.
Abstract: Background and aims: We aimed to study subclinical non-invasive vascular markers as predictors of incident long-term cognitive impairment in a longitudinal population-based study. Methods: The Barcelona-Asymptomatic Intracranial Atherosclerosis (AsIA) study is a population-based study that included a random sample of 933 Caucasian subjects (mean age 66 years, 64% male) with a moderate-high vascular risk and without history of stroke or dementia. Subclinical carotid and intracranial stenosis was assessed at baseline visit by cervical and transcranial color-coded duplex (TCCD) and confirmed by magnetic resonance angiography. Cervico-cerebral stenosis (CCS) was defined as the presence of extra and/or intracranial stenosis >50%. Baseline middle cerebral artery pulsatility index (MCA-PI) was measured bilaterally by TCCD, and mean PI of both sides was considered for analyses. Subjects were followed-up to determine incident long-term cognitive impairment (mild cognitive impairment or dementia). Results: After a median of 7.16 [6.91–7.75] years of follow-up, 91 subjects (9.7%) developed cognitive impairment, 27 of them mild cognitive impairment, and 64 dementia. Incidence of cognitive impairment was significantly higher among subjects with subclinical CCS (21.4% versus 9% in those without CCS) and among those with mean MCA-PI>1 (13.5% versus 7.4% in those with MCA-PI<1). In multivariate Cox regression analyses, both CCS and MCA-PI>1 were independently associated with incident cognitive impairment with HR of 2.07 [1.11–3.88] and 1.58 [1.02–2.46], respectively. Conclusions: Subclinical cervico-cerebral stenosis and higher MCA-PI are non-invasive neurosonological markers of incident long-term cognitive impairment in our population. Graphical abstract: Image 1 Highlights: We evaluated non-invasive sonographic predictors of incident cognitive decline. Subclinical cervico-cerebral stenosis was a predictor of long-term cognitive decline. Intracranial pulsatility index behaved as a predictor of cognitive impairment.